Do investors value companies' mandatory nonfinancial risk disclosure? An empirical analysis of the Italian context after the EU Directive. (27th April 2020) - Veltri, Stefania; De Luca, Francesco; Phan, Ho‐Tan‐Phat
Abstract: In October 2014, the European Union adopted Directive 2014/95/EU (hereafter, EU Directive), mandating companies of a certain size to draft and publish corporate nonfinancial information (NFI) regarding society and the environment. In this study, we examine the mandatory disclosure of nonfinancial (NF) risks by listed Italian companies, as required by the EU Directive, focusing on both the state‐of‐the‐art of such disclosure and its usefulness for investors. For this purpose, the study adopts a two‐staged research approach; in the first stage, we employed a manual meaning‐oriented content analysis to investigate the NF declarations (NFDs) of the listed Italian companies that were obliged to disclose NFI, returning a quality NF risks disclosure index. In the second stage, we used the value relevance methodology to investigate whether the disclosed NF risk information affects the levels of equity prices, through a modified Ohlson model. Our research is one of the first to investigate the value relevance of mandatory disclosures of NF risks following the implementation of the EU Directive, in the Italian context. The research was carried out in 2017, the first year of the directive's application for listed Italian companies. The main findings support a positive association between NF risk information disclosure levels and companies' market value. Moreover, they provide evidence of a significant mediating effect of NF risk on the relationship between financial risks and market value.